Beam-to-Column Connections with Demountable Energy Dissipative Plates - Venghiac, Vasile-Mircea; Staşcov, Mihail; Budescu, Mihai (Frontiers in Built Environment, 2018)
The behavior of steel structures subjected to seismic actions depends directly on the connections behavior. There are two current tendencies for ensuring the structural ductility: allowing the formation of plastic hinges in the beams by using reduced beam sections (RBS) or reduced web sections (RWS) or by ensuring the plastic hinge formation in the connection by using dissipative elements. This paper presents a new perspective regarding the energy dissipation mechanism formation within the beam-to-column connection. The design of connections capable of dissipating large amounts of energy, with an acceptable strength and ductile behavior is a real challenge for engineers. Sustainability is a big advantage for these connections. Another big advantage is the possibility of restoring the functionality of the damaged construction in a short time interval and with reduced costs. The introduction of connections with demountable energy dissipative plates can be a step forward in designing new beam-to-column connections for steel structures.